PERIOPERATIVE EFFECTS OF CO-ADMINISTRATION OF TCI PROPOFOL COMBINED WITH CLONIDINE AND KETAMINE - Aryabiantara, I Wayan; Sinardja, I Ketut; Sutawan, Ida Bagus Krisna Jaya; Sinardja, Cynthia Dewi; Parami, Pontisomaya; Ryalino, Christopher; Junaedi, Made Darma (Bali Journal of Anesthesiology, 2018)
Background: Propofol is often used in Total Intravenous Anesthesia (TIVA). Studies found that adding clonidine and ketamine can increase the potential to achieve an adequate level of anesthesia while reducing inflammation and post-operative pain. The goal of this study is to see if the combination of Target Controlled Infusion (TCI) propofol plus clonidine and ketamine is more effective in reducing the IL-6 level, maintaining intraoperative stability, and reducing postoperative pain and morphine consumption.Methods: Forty patients planned for major oncology surgery were divided into two groups. The treatment group (Group T) received pre-medication with clonidine, induction with TCI propofol, and intraoperative ketamine. The control group (Group C) received normal saline solution.Results: The difference of IL-6 level increase between the two groups was not statistically significant (13.6 vs. 16.6 pg/mL, p>0.05). Mean systolic blood pressure (SBP) and mean arterial pressure (MAP) in group T were higher in 5 and 10 minutes after incision, but lower in minutes 30, 60, and 120 (p <0.05). Heart rate in group T was higher in minutes 5, 10, 15, 30, 60, and 120. Visual analog scale (VAS) in 4, 8, 12, and 24 hours post-surgery were lower in group T compared to group C. And post-operative morphine consumptions in group T were also lower. (3.6 Â± 1.5 vs 9.9 Â± 3.3, p <0.05).Conclusion: TIVA using TCI propofol combined with preoperative clonidine and intraoperative ketamine is effective in maintaining hemodynamic stability, reducing post-operative and reducing morphine consumption compared to TCI propofol alone.